Enhanced near-room-temperature thermoelectric performance in GeTe - Tan, Xian Yi (2022)
GeTe is an excellent mid-temperature thermoelectric material with high dimensionless figure of merit (ZT) values at temperatures over 600 K. Its near-room-temperature performance is less studied due to the intrinsic high carrier concentration. Here, we successfully enhance the Seebeck coefficient of GeTe from ~ 30 to 220 μV·K−1 at 300 K, which is achieved by AgInSe2 alloying and Bi doping. It is demonstrated that Bi doping helps to optimize the Seebeck coefficient without deteriorating the intrinsic electrical transport properties of the matrix. A high room-temperature power factor (PF) of ~ 11 μW·cm−1·K−2 is achieved for a wide range of Bi-doped samples. The simultaneously introduced abundant point defects cause mass and strain fluctuations, which decrease the lattice thermal conductivity (κL) to a low value of 0.6 W·m−1·K−1 at 300 K. Due to the synergetic effects of Bi doping in AgInSe2-alloyed GeTe, a high room-temperature ZT value of 0.46 is obtained together with a high ZT value of 1.1 at 523 K.